Mother’s Challenges of Achieving Digital Security in Information Revolution for Primary School Children (Journal of the College of Education for Women, 2024)
The current paper aims to identify: - 1- Mother's challenges in achieving digital security for primary school children in the light of the information revolution 2- Are there statistically significant differences on the digital security scale according to the mother's educational attainment variable (elementary - intermediate - preparatory - bachelor's degree and above)? 3- Are there statistically significant differences on the digital security scale according to the mother's age variable (26-30, 31-35, 36-40, 41-45)? The research sample included (633) mothers of primary school children in Baghdad Governorate, who were selected randomly from the schools of the six directorates. The researchers constructed a scale consisting of (30) paragraphs distributed equally over the three areas: the first area (the mother's challenges in protecting the child from the risks of displayed digital content), the second area (the mother's concerns in protecting the child from the risks of connecting to the Internet), and the third area (the mother's challenges in protecting the child from the risks of bad behavior). The psychometric properties of the questionnaire (distinction, validity, reliability) were extracted. The results showed that the mother faces challenges in protecting the child to an above-average degree, and that the risks of connecting to the Internet were the most challenging, then the risks of displayed digital content, then the risks of bad behavior. There are no statistically significant differences according to the mother's educational attainment variable, and the mother's age variable.